EXAMEN ESPECIAL A LAS INVERSIONES EN BIENES DE LARGA DURACIÓN DE LA EMPRESA PÚBLICA “VIALSUR E.P” DEL GOBIERNO PROVINCIAL DE LOJA, PERIODO 2019 - Vera Armijos, Lady Gabriela (2021)
The present research work called SPECIAL EXAMINATION "TO THE INVESTMENTS IN LONG-TERM GOODS OF THE PUBLIC COMPANY "VIALSUR EP" OF THE PROVINCIAL GOVERNMENT OF LOJA, FOR THE PERIOD FROM JANUARY 1st TO DECEMBER 31st, 2019", is aimed at determining the treatment, administration and control of assets in the development of institutional activities, through the application of physical findings necessary to know the current status and existence of assets, determining the reasonableness of the balances presented in the Financial Statements; and the results in the special examination report. The audit process was carried out in three phases, first the Planning, in which information and knowledge of the institution, functional and process organic structure, mission, vision and objectives, main functions, reliability of the information of the financial management system, human and technological resources were gathered. Second, the Execution, phase in which the evaluation of the internal control was carried out through the application of questionnaires, whose result allowed to know the levels of confidence, inherent risk and control, which consequently allowed to determine the focus of the audit, the procedures and their depth; the procedures established in the preliminary and specific planning were applied; the physical verifications to the long-lasting assets were formalized to verify the real existence of the same and their correct registration, this activity was correctly fulfilled with the verification carried out of the list of Fixed Assets presented by the institution. To obtain the results, compliance and substantive procedures were applied, such as the verification of compliance with legal and regulatory standards through analytical and summary reports, which are supporting working papers; in addition, the deficiencies found 5 were supported with certified documents, where the audit statements are evidenced, which is the legal technical mechanism that the auditor in the professional exercise presents to the administration of the entity. Finally the general report was elaborated, in the phase of Results in which the deficiencies that need to be corrected and the responsibility of the servants in charge of the processes that were observed were revealed, with the purpose of issuing the report with the conclusions and recommendations to be implemented by the directive level of the company.